Association of longitudinal left atrial strain with mortality after tricuspid valve surgery - Jeong Hun Seo; Ilkun Park; Sung‐Ji Park; Dong Seop Jeong; Minjung Bak; Jihoon Kim; Eun‐Kyoung Kim; Sung‐A Chang; Su Ryeun Chung; Kiick Sung; Sang‐Chol Lee; Seung Woo Park (ESC Heart Failure, 2022)
Abstract Aims Tricuspid valve (TV) surgery for functional tricuspid regurgitation (TR) is becoming more common, but the associated mortality remains high. Therefore, we evaluated the clinical and echocardiographic parameters associated with all‐cause mortality in patients with severe functional TR who underwent TV surgery. Methods and results A total of 286 patients with severe functional TR who underwent TV replacement or repair was analysed between January 2006 and December 2017. We assessed changes in conventional echocardiographic parameters and strain, such as peak atrial longitudinal strain (PALS). During a median follow‐up period of 5.3 years, 71 (24.8%) patients died due to any cause. When comparing groups with and without all‐cause deaths, there were no significant differences in terms of sex, co‐morbidities, medication use, and surgery type. However, patients who died were older and more likely to have refractory atrial fibrillation (AF). With multivariate Cox modelling, age >65 years (adjusted hazard ratio [HR], 2.81, 95% confidence interval [CI], 1.59–4.96; P < 0.001), refractory AF (adjusted HR, 2.84, 95% CI, 1.36–5.94; P = 0.006), lower albumin level (adjusted HR, 0.50, 95% CI, 0.31–0.82), and reduced PALS (adjusted HR, 1.87, 95% CI, 1.06–3.33; P = 0.032) were significant determinants of all‐cause mortality. PALS decline was associated with refractory AF (adjusted HR, 5.74, 95% CI, 2.81–11.7; P < 0.001) and the absence of a Maze procedure (adjusted HR, 2.95, 95% CI, 1.51–5.78; P = 0.002). Conclusions A reduction in PALS was significantly associated with all‐cause mortality in our cohort of patients with severe functional TR who underwent TV surgery. This phenomenon is related to refractory AF and more aggressive intervention for AF is necessary concomitant with TV surgery.